Rapid Appraisal of the State of Competition in the Rice Value Chain - Beulah Dela Pena (Philippine Institute for Development Studies (PIDS), 2014)
The rapid appraisal is based on the interview of select players in various levels of the palay/rice value chain from Pangasinan and Nueva Ecija to Metro Manila. It finds that the paddy and rice supply chain is multilayered with many competing players in each layer, and with no evidence of any cartel-like behavior in the areas studied. Margins are limited to 2 percent or less of raw materials at all levels before retail. Profits are enhanced by volume, fast turnover of stocks, integration of operations across levels, and investments for quality consistency. The greatest threats to current players are weather risks and continuing tight local paddy supplies that spawn greater competition and increase management costs. The increased costs also highlight the lower cost option of bringing in foreign rice, which, given government quantitative restrictions on rice imports, manifests in rampant smuggling.
Keywords: 330; competition; rice sector; Philippines; paddy; supply chain; rice value chain